2021
DOI: 10.21608/jppp.2021.193801
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parasitoids, Conventional Insecticides and Ecdysone Agonists in Regulating Population of Cassida vittata Vill in Egyptian Sugar Beet Fields

Abstract: This study was carried out at the experimental farm of Sakha Agricultural Station, Kafr El-Sheikh Governorate for three successive seasons (2017/2018, 2018/2019 and 2019/2020). The study aimed to monitor seasonal abundance of Cassida vittata Vill. (Coleoptera: Chrysomelidae) and its hymenopterous parasitoids, Monorthochaeetaa nigra Blood (Trichogrammatidae) and Dinarmus laticeps (Pteromalidae). Further, role of ecdysone agonists compounds in reducing C. vittata numbers and their adverse effect on these parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In Egypt, the status of insect predators and parasitoids in sugar beet fields was investigated by several authors (Abo-Saied Ahmed, 1987;Youssef, 1994;El-Agamy, et. al., 1996;Awadalla, 1997;Abou-Attia, 1999;Bazazo, 2005 andFatma H. Hegazy andEl-Sheikh, 2021) Formicid species are very effective biocontrol agents for several reasons; colonies contain large numbers of individuals that consume large populations of prey and their predation is not limited to a particular prey species or stage (Paulson and Burts, 1993). As well, in many countries, several studies have demonstrated that ants can be key generalist predators of crop pests (El-Keroumi et al, 2010;Fernandes et al, 2010 andSanders &Van Veem, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, the status of insect predators and parasitoids in sugar beet fields was investigated by several authors (Abo-Saied Ahmed, 1987;Youssef, 1994;El-Agamy, et. al., 1996;Awadalla, 1997;Abou-Attia, 1999;Bazazo, 2005 andFatma H. Hegazy andEl-Sheikh, 2021) Formicid species are very effective biocontrol agents for several reasons; colonies contain large numbers of individuals that consume large populations of prey and their predation is not limited to a particular prey species or stage (Paulson and Burts, 1993). As well, in many countries, several studies have demonstrated that ants can be key generalist predators of crop pests (El-Keroumi et al, 2010;Fernandes et al, 2010 andSanders &Van Veem, 2011).…”
Section: Introductionmentioning
confidence: 99%